Smart business : - Zeng, Ming (Harvard Business Review Press, 2018)
Executives already know that the classic approach to strategy--analyze, plan, execute--is losing relevance as the business landscape becomes more interconnected and automated. But they don't yet know what replaces the traditional strategy toolkit. Some executives even think that strategy is dead. According to Ming Zeng, the Chief Strategy Officer of the Alibaba Group, strategy is decidedly not dead, but it is radically changed. He has spent over a decade observing how companies in the Alibaba Group and the firms it does business with are becoming "smarter," through interconnected networks that facilitate hundreds of thousands of simultaneous interactions every second and the algorithms that learn from all those interactions to automatically and continually improve the decisions and actions companies take on behalf of serving their customers. Zeng explains how strategy is fundamentally redefined--bearing little resemblance to the principles, practices, and frameworks he learned as a PhD student and then taught as a professor in academic institutions around the world--when companies are "smart." Revealing the revolutionary practices that he and his team have adopted at Alibaba to leverage these technological trends, Smart Business provides the new toolkit for formulating and executing strategy. Informed by the cutting-edge practices of Alibaba and other companies around the world, this book builds on the author's previous academic research to put Alibaba's strategies and approaches into a broader context that applies to all businesses, not just internet companies or startups. The result is a book that describes a radical new approach to strategy and shows how companies everywhere can apply it.